Do psychiatrists sufficiently understand the statistical measures used in clinical research? - Kunwar, AR (Journal of Psychiatrists' Association of Nepal, 2014)
DOI: http://dx.doi.org/10.3126/jpan.v1i1.9924 Journal of Psychiatrists' Association of Nepal Vol.1(1) 2011: 24-25